1958, o ano que não terminou: memória e performance na cena do baile black nostalgia paulistano - D'Allevedo, Pedro Tadeu Faria (2017)
This inquiry treats of the black dance nights that take place in São Paulo, aiming to understand such event’s structuring as a cultural movement widely diffused through the city’s urban space. The study carries out a sociological analysis of the musical-cultural scene fashioned in by such festival, which is a kind of dancing party currently known as “nostalgia dance”. If first appeared in the city in 1958 and was called simply a ball until the beginning of the 1980s, when it received its current appellation. With peculiar form and contents, this phenomenon is produced and enjoyed by São Paulo’s Afrodescendants. Structured as a dancing leisure, it spreads out a hybrid musical consumption, with special emphasis on music and rhythms from the past, combining, by these means, leisure and economic activity. Most of the music comes from North-American culture and the rhythms may be danced in couples, individually or in groups, according to the party’s mood. The repertoire comprehends genres such as jazz swing, rock’n roll, samba, sambalanço (a kind of samba swing), funk, soul, rap and rhythm’n’blues. A new, specific kind of dancing was invented around it, resulting from a mix of its usual rhythms: the samba-rock. During the 1970s it partly gave way to the funk-soul dance, but continued to exist in parallel with it. Nostalgia dance is widely appreciated by adults from the abovementioned social group. Such individuals constitute a collectivity with an affective basis, cultivating a taste for past times’ music and dancing. The scene gained new impetus during the 1990s, greatly intensified during the 2000s due to renewed interest for samba-rock. Characterized by a peculiar aesthetical and behavioral pattern that follows closely that shaped in its origin, it is a dancing party recurrent in the time and inherent to São Paulo’s Afrodescendant community. Our objective is to analyze the sociocultural practices associated with these parties, considering they are very meaningful events, affirmative not only of Afrodescendants’ existing identity, but also of that which is in elaboration, and displays the symbols of ethnicity that mark the difference between “us” and “them”. The study develops itself by means of ethnographic proceedings. Participant observation provides a privileged point of view, both close and from within, crystalized in the interlocutor’s dialogical relation. It intends, finally, to elaborate a transversal analyses of the phenomenon by means of four reflexive concepts: performance, scene, generation and memory.